(untitled) (Journal of the College of Basic Education, 2026)
The violence to which family members are exposed to many reasons، some of which are related to the surrounding environment، some of which relate to the same person’s violence، some of which relate to the victim and in return for these reasons there must be a treatment for them in light of the purposes of the glorious Sharia، and has highlighted the causes of domestic violence and the methods leading to his treatment in the shadow of The purposes of Sharia.